The timing of booster sessions may not improve resuscitation skill retention among healthcare providers: a randomized controlled trial (Canadian Medical Education Journal, 2023)
Introduction: Booster sessions can improve cardiopulmonary resuscitation (CPR) skill retention among healthcare providers; however, the optimal timing of these sessions is unknown. This study aimed to explore differences in skill retention based on booster session timing.Methods: After ethics approval, healthcare providers who completed an initial CPR training course were randomly assigned to either an early booster, late booster, or no booster group. Participants’ mean resuscitation scores, time to initiate compressions, and time to successfully provide defibrillation were assessed immediately post-course and four months later using linear mixed models.Results: Seventy-three healthcare professionals were included in the analysis. There were no significant differences by randomization in the immediate post-test (9.7, 9.2, 8.9) or retention test (10.2, 9.8, and 9.5) resuscitation scores. No significant effects were observed for time to compression. Post-test time to defibrillation (mean ± SE: 112.8 ± 3.0 sec) was significantly faster compared to retention (mean ± SE: 120.4 ± 2.7 sec) (p = 0.04); however, the effect did not vary by randomization.Conclusion: No difference was observed in resuscitation skill retention between the early, late, and no booster groups. More research is needed to determine the aspects of a booster session beyond timing that contribute to skill retention.